Problem-oriented computer system with load control to complex computational works - Poźniak, Iwona (Zielona Góra: Uniwersytet Zielonogórski)
Balancing the workload among processors is of fundamental importance to the efficient utilization of a local computer network. In the paper some ideas from control area are applied to improve load-balancing for problem-oriented complex works which are composed of sequences of dependent tasks.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka